Mediation as a tool in Foreign Policy - Noyola Cuello, Mauricio de Jesús (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Conflict is a historical constant and a natural expression of individual and group differences. This diversity of ideas, beliefs and aspirations fuels confrontation, making conflict a catalyst for transformation and change. Disputes, from tribal to ideological, drive re-evaluation and adaptation, fostering innovation. Societal development adds new dimensions to conflicts, which now encompass wars, political divisions and social tensions, intensified by power struggles and limited resources. Despite its pervasive nature, it is essential to understand and address conflict, seeing it as an opportunity for growth and continuous improvement. After World War II, structures were established for the resolution of international disputes, such as the UN, which promotes peace and security. The use of Alternative Dispute Resolution (ADR) has been internationally recognized for facilitating quick and satisfactory responses to disputes, avoiding protracted litigation and benefiting the most vulnerable. Institutions such as the UN, OAS, AU, EU, ICJ and ICSID play key roles in mediation and dispute resolution. Mediation, as a diplomatic means, allows the parties to maintain their freedom of action and decision. In foreign policy, Mexico faces challenges with the United States on issues such as energy, climate change, migration and drug trafficking, where mediation can be key to consolidate and strengthen relations. The North American Leaders Summit facilitates dialogue and problem solving, addressing crucial issues such as migration, sustainable development, security and trade. Mediation can accelerate decision-making, preserve diplomatic relations and strengthen trust between countries, promoting lasting and satisfactory solutions.